Corporate Social Responsibility and Team Performance: The Mediating Role of Team Efficacy and Team Self-Esteem - Lin, Chieh-Peng; Baruch, Yehuda; Shih, Wei-Chi (2012)
This study examines the influence of three components of corporate social responsibility on team performance. In the proposed model of this study, team performance is indirectly affected by three dimensions of perceived corporate citizenship (i.e., economic, legal, and ethical citizenship) via the mediation of team efficacy and team self-esteem. Surveying members of 172 teams confirms most of our hypothesized effects. Our results show that economic citizenship influences team performance via the mediation of both team efficacy and team self-esteem. However, legal citizenship influences team performance via team efficacy alone, whereas ethical citizenship influences team performance only via team self-esteem. We discuss the theoretical and managerial implications of our findings.
Keywords: Discretionary citizenship; Ethical citizenship; Team efficacy; Team performance; Corporate Citizenship; Corporate Social Responsibility